Holy Sacraments from a legal and historical point of view - ZABOROWSKI, MAREK (Prawo Kanoniczne, 2012)
The above analysis suggests that sacraments are the essence of Christian life. Although it is impossible to define them precisely, over a span of history theologians attempted to provide some designations of what they [the sacraments] are and what their role in a life of a Christian is. The Catechism of the Catholic Church did not provide such a definition either. It listed the sacraments and indicated their connection with everyday life of a Christian. The question of how to administer and receive sacraments is specified in the Codes of Canon Law of 1917 and of 1983.The legislators of the two Codes emphasize explicitly that it was Jesus who established the sacraments and they [the legislators] call them the main means of sanctifying which should be administered and received with respect and diligence.